2021
DOI: 10.1002/anie.202015411
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Spiro‐Axis Induced Blue Thermally Activated Delayed Fluorescence Material for Efficient Circularly Polarized OLEDs with Low Efficiency Roll‐Off

Abstract: A spiro‐axis skeleton not only introduces circularly polarized luminescence (CPL) into thermally activated delayed fluorescence (TADF) molecules but also enhances the intramolecular through space charge transfer (TSCT) process. Spiral distributed phenoxazine and 2‐(trifluoromethyl)‐9H‐thioxanthen‐9‐one‐10,10‐dioxide act as donor and acceptor units, respectively. The resulting TADF enantiomers, (rac)‐OSFSO, display emission maxima at 470 nm, small singlet‐triplet energy gap (ΔEST) of 0.022 eV and high photolumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(65 citation statements)
references
References 69 publications
1
64
0
Order By: Relevance
“…More recently, based on the strategy of space charge transfer, Zheng's group [330] reported one pair of blue TADF enantiomers (R/S)-106 with central chirality, in which the donor of phenoxazine subunit and the receptor of sulfone moiety was connected by the spiro-carbon centre. It was found that the ΔE ST of the enantiomers was 0.022 eV, and PLQY in the doped film was as high as 81.2%.…”
Section: Cp-oleds Based On Chiral Tadf Moleculesmentioning
confidence: 99%
“…More recently, based on the strategy of space charge transfer, Zheng's group [330] reported one pair of blue TADF enantiomers (R/S)-106 with central chirality, in which the donor of phenoxazine subunit and the receptor of sulfone moiety was connected by the spiro-carbon centre. It was found that the ΔE ST of the enantiomers was 0.022 eV, and PLQY in the doped film was as high as 81.2%.…”
Section: Cp-oleds Based On Chiral Tadf Moleculesmentioning
confidence: 99%
“…However, the reduction behaviors of Ir(III) complexes were irreversible, so we were unable to estimate their HOMO and LUMO energies accurately [ 36 ]. According to the equations E HOMO = −( E ox − E Fc/Fc + + 4.8) eV, E gap = 1240/λ abs-onset , and E LUMO = E HOMO + E gap , the HOMO levels for Ir(III) complexes were estimated on the basis of an oxidation potential of 4.8 eV (below vacuum level) for Fc + /Fc, the LUMO levels were estimated on the sum of HOMO levels, and the energy band gap was determined by absorption edge (MLCT) in the absorption spectrum [ 20 , 37 , 38 ]. The 3 MLCT absorption bands of the three iridium complexes reached the absorption edge and thus mainly participated in the electron semiconductivity [ 39 ], which was in agreement with the calculation results of the frontier molecular orbital distributions and energy splitting of singlet and triplet states of Ir-3 ( Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…b) Corresponding HOMO and LUMO distributions and calculated energy levels (DFT with B3LYP functional and the 6-31G(d) basis set). [16] Angewandte Chemie Zuschriften Information, Table S3). The HOMO and LUMO energies from DFT calculations are À5.19 and À1.43 eV, respectively.…”
mentioning
confidence: 99%